DESAIN SPOT HASTA KARYA KREATIF PADA AREA WISATA PENTUNGAN SARI SEBAGAI PENUNJANG DESA WISATA TOYOMARTO-SINGOSARI - Setiawati, Eti; Sukmawan, Sony; Zakiyah, Millatuz; Fauzi, Nanang Bustanul (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service project is based on the partner's need for the development of tourist attractions for the Grama Tirta Tourism Village in Toyomarto Singosari. The development of tourist attractions is directed at developing creative craft spot designs to strengthen the capacity of Toyomarto Village as a tourism village. Therefore, this community service project aims to develop creative craft spot designs and create creative craft spots in collaboration with the Toyomarto Village Government. The methods used to achieve this objective include surveys and observations as preliminary studies, followed by focus group discussions (FGD) with relevant parties (the village, expert team, and service project team) to formulate the design of creative handicraft spots, determine the appropriate location, and agree on various technical aspects related to the creation of creative handicraft spots. Finally, the project concluded with a symbolic handover and evaluation of the creative craft spot. The outputs of this community service project include an article on the project's findings and a documentary video/news report in the media.